Laboratory modeling of thermal and temporal cracking in swelling clays - Zhang, Gang; Jaffar, Syed Taseer Abbas; Israr, Jahanzaib; Atta, Muneeb; Jafri, Turab (Frontiers in Earth Science, 2023)
Crack development under changing environment is the controlling factor for stability and strength of expansive soils. Expansive soils exhibit large volumetric changes with changes in their moisture conditions that may occasionally lead to reduced bearing capacity and foundation failures. This study purports to model the crack initiation and its spatial progression in relation to moisture content and drying period, respectively. Volumetric soil shrinkage is determined using high-definition Digital Camera Imaging and Vernier scale methods, while the soil settlement under vertical shrinkage deformation could be captured through a tensile stress model for soils. It was revealed that a small change in suction could trigger the crack initiation, which would propagate further under different environmental conditions. Further, it was observed that the crack volume increased rapidly at a specific moisture content and could penetrate as deep as 1 m after nearly 1.5 months that is fully consistent with the current model predictions. Nevertheless, the findings from this study could be implicated to quantify the detrimental behavior of expansive soil present in pavement subgrades and shallow foundations for light-weight structures.